Self-Supervised Learning from Images with a Joint-Embedding Predictive Architecture - Assran, Mahmoud; Duval, Quentin; Misra, Ishan; Bojanowski, Piotr; Vincent, Pascal; Rabbat, Michael; LeCun, Yann; Ballas, Nicolas (Proceedings (IEEE Computer Society Conference on Computer Vision and Pattern Recognition. Online), 2023)
This paper demonstrates an approach for learning highly semantic image representations without relying on hand-crafted data-augmentations. We introduce the Image-based Joint-Embedding Predictive Architecture (I-JEPA), a non-generative approach for self-supervised learning from images. The idea behind I-JEPA is simple: from a single context block, predict the representations of various target blocks in the same image. A core design choice to guide I-JEPA towards producing semantic representations is the masking strategy; specifically, it is crucial to (a) sample target blocks with sufficiently large scale (semantic), and to (b) use a sufficiently informative (spatially distributed) context block. Empirically, when combined with Vision Transformers, we find I-JEPA to be highly scalable. For instance, we train a ViT-Huge/14 on ImageNet using 16 A100 GPUs in under 72 hours to achieve strong downstream performance across a wide range of tasks, from linear classification to object counting and depth prediction.